English language proficiency according to the common European framework of reference CERF of second year's students of Ismael Pérez Pazmiño high school in Machala city, in the school year 2014 - 2015. - Correa Samaniego, Cristhian Alejandro; Montalván Manzanillas, Carlos Luis; Plaza Zambrano, Argenis Fernando (My University, 2014)
La presente tesis se enfoca a conocer el nivel de proficiencia del idioma inglés acorde a los estándares de educación establecidos por el Ministerio de Educación según el marco común Europeo de referencia en la enseñanza del idioma como segunda lengua. Esta investigación se desarrolló en el colegio "Ismael Pérez Pazmiño" y realizó a los estudiantes y profesores del segundo año de bachillerato como objetos de estudio.
This thesis focuses on knowing the level of English proficiency according to the education standards set by the Ministry of Education under the European common frame of reference in teaching as a second language . This research was conducted at school, " Ismael Perez Pazmiño " and made students and teachers of the second year of high school as objects of study.
Keywords: LANGUAGE; ACCORDING; STUDENT; SCHOOL